LASIS-Assisted Copper Nanoparticle Synthesis and Characterization, along with UV-Visible Spectroscopy - Chaitanya Patel (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study investigates the creation of copper nanoparticles (CuNPs) using chemical reduction and laser ablation in liquid (LASIS). UV-visible spectroscopy is used to examine the optical characteristics of the nanoparticles created by these techniques. The purpose of the study is to compare the stability, efficacy, and particle size of CuNPs produced using different techniques. When comparing the LASIS method to the chemical reduction process, Transmission Electron Microscopy (TEM) examination revealed that the former produced smaller and more uniform nanoparticles. This work demonstrates the effectiveness of both synthesis techniques, with LASIS clearly outperforming the other in the production of superior CuNPs with more control over particle size and dispersion. A thorough explanation of the chemical reduction method and LASIS used in the synthesis of copper nanoparticles is provided, and UV-visible spectroscopy is used to characterize the resulting particles.
Keywords: Nanoparticles; Copper Nanoparticles; LASIS; Chemical Reduction Method